Murepavadin, a Small Molecule Host Defense Peptide Mimetic, Activates Mast Cells via MRGPRX2 and MrgprB2 - Amponnawarat, Aetas; Chompunud Na Ayudhya, Chalatip; Ali, Hydar (Frontiers in Immunology, 2021)
Pseudomonas aeruginosa is a common cause of nosocomial skin wound infection and presents a therapeutic challenge due to its ability to form biofilms and to develop antibiotic resistance. In mouse skin, mast cells (MCs) contribute to both bacterial clearance and wound healing following P. aeruginosa infection via an unknown mechanism. We have recently shown that host defense peptides (HDPs) induce degranulation in human MCs via Mas-related G protein-coupled receptor X2 (MRGPRX2). Small molecule HDP mimetics have distinct advantages over HDPs because they are inexpensive to synthesize and display high stability, bioavailability, and low toxicity. Murepavadin is a lipidated HDP mimetic, (also known as POL7080), which displays antibacterial activity against a broad panel of multidrug-resistant clinical isolates of P. aeruginosa. We found that murepavadin induces Ca2+ mobilization, degranulation, chemokine IL-8 and CCL3 production in a human MC line (LAD2 cells) that endogenously expresses MRGPRX2. Murepavadin also induced degranulation in RBL-2H3 expressing MRGPRX2 but this response was significantly reduced in cells expressing missense MRGPRX2 variants within the receptor’s ligand binding pocket (G165E) or G protein coupling domain (V282M). Compound 48/80 induced β-arrestin recruitment as measured by transcriptional activation following arrestin translocation (Tango) and promoted receptor internalization, which resulted in substantial decrease in the subsequent responsiveness to the MRGPRX2 agonist. By contrast, murepavadin did not cause β-arrestin-mediated MRGPRX2 regulation. Murepavadin induced degranulation in mouse peritoneal MCs via MrgprB2 (ortholog of human MRGPRX2) and caused increased vascular permeability in wild-type mice but not in MrgprB2-/- mice. These findings demonstrate that murepavadin activates human and murine MCs via MRGPRX2 and MrgprB2, respectively and that MRGPRX2 is resistant to β-arrestin-mediated receptor regulation. Thus, in addition to its direct activity against P. aeruginosa, murepavadin may contribute to host defense and wound healing by harnessing MC’s immunomodulatory property via the activation of MRGPRX2.